An analytical tool for computing perimeter based on visual and coordinates analysis - Salim Nasir, Mohd Agos; Sadikin, Zubaidah; Panji, Elaziera; Mohd Rohaidi, Nur Nadhirah; Harun, Nurzalina; Rathi, Sidik (Academica Press Solutions, 2024)
Perimeter calculation, a fundamental aspect of geometric analysis, plays a crucial role in numerous fields, ranging from architecture and engineering to urban planning and environmental assessment. Traditionally, manual methods for computing perimeters have been fraught with challenges, often requiring significant time investment and susceptible to errors, particularly when dealing with irregular shapes. The introduction of PeriGo represents a paradigm shift in perimeter calculation, offering an innovative software solution that streamlines the process through its user-friendly graphical interface. Leveraging advanced mathematical algorithms, including a straightforward formula for determining distances between points, PeriGo ensures precise results while mitigating the risk of human error. This transformative tool promises to revolutionize perimeter calculation across diverse industries, empowering users with accurate and efficient calculations in a fraction of the time. With its intuitive interface and robust functionality, PeriGo emerges as an indispensable asset for professionals seeking reliable geometric analysis. Moreover, recent research highlights the significance of algorithmic approaches in enhancing precision in geometric analysis, emphasizing the importance of user interface design considerations for geometric analysis software tools.